PENANGANAN TINDAK PIDANA KEKERASAN TERHADAP PEREMPUAN DAN ANAK DALAM PERSPEKTIF KRIMINOLOGI (STUDI PADA UNIT PPA SATRESKRIM POLRES BLITAR) - Eko Budi Sariyono; Dian Cahayani; Arum Widiastuti (JISOS: JURNAL ILMU SOSIAL, 2024)
All forms of violence in general and acts of violence against women and children are a form of violation of human rights and constitute a crime against human dignity and discrimination. The state is responsible for the protection, promotion, enforcement and fulfillment of human rights guaranteed by laws and regulations. This research discusses the factors causing criminal acts of violence against women and children as well as the handling of criminal acts of violence against women and children by the women and child protection unit of the Blitar Police Criminal Investigation Unit. The type of research used in this writing is empirical juridical research to determine the conditions that occur in the field. The research approach uses a qualitative approach with the legal materials used being primary, secondary and tertiary legal materials. The results of this research show that the factors causing criminal acts of violence against women and children in the Blitar Regency area are legal awareness, patriarchal culture, economic factors and poverty, allegations of infidelity and early marriage factors. From this research it can be explained that the handling efforts were carried out using a non-penal and penal approach and the obstacles experienced were in the form of internal and external obstacles from the police